'Bom Bombed Kwin': How Two Card Games Model Kula, Moka, and Goroka. Issue 3 (November 2014) - Pickles, Anthony J.; Pickles, Anthony J
Abstract In 2009–2010, in Goroka, I studied card games that had a lineage traceable to a common ancestor called laki. Two games were dominant: kwin (queen) and bom (bomb).1 Both allowed players to test and act upon their efficacy, detect the disruptive negative thoughts of others, and cultivate the thoughts seen as essential to success. Yet the games' characters were contrasted: one was slow, the other fast; one is long‐standing, the other a craze; one for the old, one for the young; one more 'Melanesian', one irresponsible. Kwin and bom are among a repertoire of indigenous 'analytics' used by people at different life‐stages; they model Goroka because they propagate the types of thought they cater to, and fall victim to that thought in turn, e.g., 'fast games' propagate 'fast thoughts' that get bored with the games' rules and invent others to take their place. This speaks to Melanesian and anthropological preoccupations with effecting innovations within, and upon, 'total systems' like the famous kula or moka. In gambling this innovatory capacity is measured by speed, providing a ready model for broader change.